Vector borne blood protozoa in pet dogs from Ipoh, Malaysia - Panchadcharam, Chandrawathani; Omar, Jamnah; Bathmanaban, Premaalatha; Ismail, Erwanas Asmar; A. K., Suliana; S. I., Sheikh Abdul Muizz; Jegathesuran, Tharshini; Hassan, Mohd Naheed (2015)
A total of 103 pet dogs of various breeds were screened for blood protozoans by thin and thick blood smear and 15 dogs were found to harbor microfilaria of Dirofilaria immitis and Erhlichia canis. Other parasites such as Leishmania, Babesia or Trypanosoma were not found indicating good tick or insect management.